For the function f(x) = 2 – 3x, find f(–4).

answer asap

Skip to content# For the function f(x) = 2 – 3x, find f(–4). answer asap

Mathematics ##
Comments (3) on “For the function f(x) = 2 – 3x, find f(–4). answer asap”

### Leave a Reply Cancel reply

For the function f(x) = 2 – 3x, find f(–4).

answer asap

F(x) = 2 - 3xf(-4) means u r subbing in -4 for every x

f(-4) = 2 - 3(-4)

f(-4) = 2 + 12

f(-4) = 14

You just have to plug in -4 into

[tex]f(x) = 2 - 3x[/tex]

This implies that,

[tex]f( - 4) = 2 - 3( - 4)[/tex]

[tex]f( - 4) = 2 + 3(4)[/tex]

[tex]f( - 4) = 2 + 12[/tex]

[tex]f( - 4) = 14[/tex]

You just have to plug in -4 into

[tex]f(x) = 2 - 3x[/tex]

This implies that,

[tex]f( - 4) = 2 - 3( - 4)[/tex]

[tex]f( - 4) = 2 + 3(4)[/tex]

[tex]f( - 4) = 2 + 12[/tex]

[tex]f( - 4) = 14[/tex]